Keluhan Musculoskeletal Disorders dan Kelelahan Kerja pada Tenaga Kerja Bongkar Muat di Pelabuhan Tenau - Civic Karani Maudy; Luh Putu Ruliati; Soni Doke (Media Kesehatan Masyarakat, 2021)
Manual material handling activity is a job related to lifting, moving, pulling, and holding goods that rely on human labor, includes loading and unloading goods at the Labor of Tenau Kupang. This research aimed to know to determine the relationship between age, smoking habit, manual material handling activity, and temperature of the environment with complaints of musculoskeletal disorders and work fatigue of the labor at Tenau Kupang Harbour. The kind of research was a quantitative study with a cross-sectional approach. The Population of this research is 36 people. The taking of the sample was done by a total sampling method that is 36 people. The test used was the Chi-square test. The results of the research showed that 21 people (58,3%) suffer from musculoskeletal disorders and 19 people (52,8%) suffer from work fatigue. The results showed that as many as 29 people (80.6%) experienced MSDs complaints and as many as 25 people (69.4%) experienced work fatigue. The analysis showed that there was no relationship between age and smoking habits with MSDs complaints, while the risk level of MMH and ambient temperature had a relationship with MSDs complaints. There is no relationship between age, smoking habits, the level of risk of MMH with work fatigue, while ambient temperature has a significant relationship with work fatigue. Therefore, it is advisable for workers to stretch their muscles during breaks so as to reduce MSDs complaints. Meanwhile, the workers cooperative union needs to provide drinking water facilities in order to reduce worker dehydration.